2003
DOI: 10.1016/s0168-6496(02)00430-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermentable carbohydrates on piglet faecal bacterial communities as revealed by denaturing gradient gel electrophoresis analysis of 16S ribosomal DNA

Abstract: The effect of fermentable carbohydrates (sugar beet pulp and fructooligosaccharides) on the faecal bacterial communities of weaning piglets was analysed using 16S rDNA-based approaches. Amplicons of the V6^V8 variable regions of bacterial 16S rDNA were analysed by denaturing gradient gel electrophoresis (DGGE), cloning and sequencing. Differences in piglet faecal bacterial community structure were determined based on the Dice coefficients for pairwise comparison of the DGGE fingerprints and revealed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 26 publications
8
36
0
Order By: Relevance
“…Nevertheless, the lack of change over time in diversity in Indoor pigs does not preclude the possibility that microbiota function was not altered. Access to substrate in Outdoor pigs was presumably the major determinant of this increased diversity, as has been reported in other studies where different diets have been offered (Konstantinov et al, 2003). Table 1 shows that there was a trend (P = 0.109) for a difference in microbial population structure depending on the type of housing they were reared in before and after weaning.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Nevertheless, the lack of change over time in diversity in Indoor pigs does not preclude the possibility that microbiota function was not altered. Access to substrate in Outdoor pigs was presumably the major determinant of this increased diversity, as has been reported in other studies where different diets have been offered (Konstantinov et al, 2003). Table 1 shows that there was a trend (P = 0.109) for a difference in microbial population structure depending on the type of housing they were reared in before and after weaning.…”
Section: Resultssupporting
confidence: 63%
“…The lack of a significant sampling site effect (P = 0.795) suggests that diversity of the microbiota along the length of the large intestine was similar, however differences in microbial community structure have been shown between the small intestine and large intestine (eg, Simpson et al, 1999;Konstantinov et al, 2003). Unfortunately we were unable to make such a comparison in our study.…”
Section: Resultsmentioning
confidence: 73%
“…This was surprising, as increased levels of saccharolytic lactobacilli are generally assumed to be associated with an increased supply of fermentable carbohydrates instead of protein [43,44]. However, it is possible that with increasing dietary levels of SBM, there was an increase in availability of free AA, such as lysine, in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…For newlyweaned piglets, the dietary supplement of fermentable carbohydrates is generally regarded as a comparatively straightforward approach to improve microbiota composition and functionality of both the small and large intestine (Williams et al, 2001;Bauer et al, 2006). Recent studies demonstrated that the addition of sugarbeet pulp, inulin, lactulose and wheat starch to the diet, designed to stimulate the fermentation along the entire gut, altered the composition of bacterial microbiota in the gut of newly-weaned piglets (Konstantinov et al, 2003(Konstantinov et al, , 2004. The supplement of inulin to different basal diets also affected the proportion of piglets with detectable levels of bifidobacteria, but not lactobacilli (Loh et al, 2006).…”
Section: Pre and Probioticsmentioning
confidence: 99%